2016
DOI: 10.1177/0963662516661292
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the influence of affect and cognition over time on consumer attitude formation toward nanotechnology: A longitudinal survey study

Abstract: Insights into how consumer attitudes toward nanotechnology are formed and develop are crucial for understanding and anticipating possible barriers in consumer acceptance of nanotechnology applications. In this study, the influence of affect and cognition on overall opinion is investigated longitudinally for emerging nanotechnologies, and compared with conventional technologies. Overall, in attitude formation toward nanotechnology applications, people rely relatively more on affect than cognition. Over time, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…This suggests that the high level of experience with social media does not detrimentally affect the generalizability of our results.Regarding the level of knowledge on nanodesigned food and the attitude toward it, the situation in the Netherlands seems to correspond to the international scene. Knowledge on nanotechnology is low and attitudes are not yet strongly established(Van Giesen, Fischer, & Van Trijp, 2018). The generalizability of our findings is thus not detrimentally affected by the level of knowledge on nanodesigned food in the Netherlands.4.3 | Implication for risk communication practiceOur study showed that social media expressions by other people without obvious expertise may affect the individual's views regarding a human enhancement technology.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…This suggests that the high level of experience with social media does not detrimentally affect the generalizability of our results.Regarding the level of knowledge on nanodesigned food and the attitude toward it, the situation in the Netherlands seems to correspond to the international scene. Knowledge on nanotechnology is low and attitudes are not yet strongly established(Van Giesen, Fischer, & Van Trijp, 2018). The generalizability of our findings is thus not detrimentally affected by the level of knowledge on nanodesigned food in the Netherlands.4.3 | Implication for risk communication practiceOur study showed that social media expressions by other people without obvious expertise may affect the individual's views regarding a human enhancement technology.…”
mentioning
confidence: 71%
“…Regarding the level of knowledge on nanodesigned food and the attitude toward it, the situation in the Netherlands seems to correspond to the international scene. Knowledge on nanotechnology is low and attitudes are not yet strongly established (Van Giesen, Fischer, & Van Trijp, ). The generalizability of our findings is thus not detrimentally affected by the level of knowledge on nanodesigned food in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, very few actors in the nanotechnology industry are realizing these principles, mostly because they are not being held accountable by societies for their decisions. Yet nanomaterials are still at an early, if rapidly evolving, stage of development: intervention now could result in risk reduction later (van Broekhuizen and Reijnders, 2011).…”
Section: Materials Sovereignty: Pathways For Shaping Nanotechnology Dmentioning
confidence: 99%
“…It shown that nanofood can improve food safety and processing, improve food quality, improve taste and nutrition, delivery procedures, broaden pathogen detection, enhance food functionality, protect the environment and cost -efficiency of storage and distribution [9]. However, the result from previous research shown that consumer understanding and knowledge are still limited and some of them are not realized the existence of nanofood [10].…”
Section: Introductionmentioning
confidence: 99%